APLIKASI BUSINESS INTELLIGENCE PENAMPIL DATA OMSET PENJUALAN USAHA MIKRO KECIL MENENGAH MENGGUNAKAN ONLINE ANALYTICAL PROCESSING DENGAN METODE GROWTH RATIO BERBASIS WEB - William Thomas; Rino (Komunitas Dosen Indonesia, 2023)
Micro, small and medium enterprises are businesses that are generally individually and are small business entities such as selling dumplings, fried bananas, even internet cafes and so on. This study aims to create a business intelligence application that displays sales turnover data for micro, small and medium enterprises using online analytical processing with a web-based growth ratio method that aims to help micro, small and medium enterprises by making application prototypes that can display data from sales results in various easy graphs. viewed and using the growth ratio formula method where the formula calculates the profit as a percentage and can be compared with the previous data. This application program is made for the public with the hope that micro, small and medium enterprises experience significant progress in profiting from their sales turnover Human-created applications were created to facilitate human needs and work ranging from lifestyle, health, security, entertainment, and others. In addition, we often also find several applications that have similarities with each other in various functions, appearance, and so on so that it spurs developers to have to work hard to develop these applications to attract the attention of website users by offering unique advantages and features that can be a differentiator from similar applications. The need for clear and precise information today is needed in everyday life in order to avoid false information or hoaxes. In addition, precise and accurate information can also be an important element that can influence developments in various aspects such as sales business, education, entertainment and so on at this time and in the future.